Blood‐Lymphatic Integrated System with Heterogeneous Melanoma Spheroids via In‐Bath Three‐Dimensional Bioprinting for Modelling of Combinational Targeted Therapy. Issue 29 (26th August 2022) - Cho, Won‐Woo; Ahn, Minjun; Kim, Byoung Soo; Cho, Dong‐Woo
Abstract: Although metastatic melanoma can be managed with chemotherapy, its heterogeneity and resistance to therapy remain poorly understood. In addition to the spread of melanoma in the bloodstream, melanoma‐stroma interaction and the lymphatic system play active roles in said heterogeneity and resistance, leading to its progression and metastasis. Reproducing the complexities of the melanoma microenvironment in vitro will help understanding its progression and enhance the translatability of potential cancer therapeutics. A blood‐lymphatic integrated system with heterogeneous melanoma spheroids (BLISH) using the in‐bath bioprinting process is developed. The process uniformly prints size‐controllable metastatic melanoma spheroids along with biomimetic blood and lymphatic vessels (LVs). The system reproduces hallmark events of metastatic melanoma, such as tumor stroma interaction, melanoma invasion, and intravasation. The application of the system to investigate the anticancer effect of combinational targeted therapy suggests that it can be used to study the pathophysiology of melanoma and improve the accuracy of drug response monitoring in skin cancer. Abstract : Melanoma‐stroma interaction and the blood‐lymphatic system play active roles in melanoma progression and metastasis. In this study, a blood‐lymphatic integrated melanoma model via in‐bath bioprinting is developed. The system reproduces hallmark events of metastatic melanoma. The application of combinational targeted therapy suggests that the developed system can be used to study the pathophysiology of melanoma and improve the accuracy of drug response monitoring in skin cancer.